Chocolate Consumption in Relation to All-Cause and Cause-Specific Mortality in Women: The Women's Health Initiative. (29th May 2020) - Sun, Yangbo; Liu, Buyun; Snetselaar, Linda; Wallace, Robert; Shadyab, Aladdin; Chen, Guo-Chong; Shikany, James; Manson, JoAnn; Bao, Wei
Abstract: Objectives: To examine the association of chocolate consumption with all-cause and cause-specific mortality. Methods: We included 84, 709 postmenopausal women free of cardiovascular disease (CVD) and cancer at baseline in the prospective Women's Health Initiative cohort who were enrolled during 1993–1998. Chocolate consumption was assessed using a validated food frequency questionnaire. These women were followed through March 2018. Results: During 1608, 856 person-years of follow up (19.0 years on average [SD = 4.2]), 25, 388 deaths occurred, including 7069 deaths from CVD, 7030 deaths from cancer, and 3279 deaths from dementia. After adjustment for a variety of covariates, compared to no chocolate consumption, the HRs (95% CIs) for all-cause mortality were 0.95 (0.92, 0.98), 0.93 (0.89, 0.96), 0.97 (0.90, 1.04) and 0.90 (0.84, 0.97) for <1 serving/week, 1–3 servings/week, 4–6 servings/week and ≥1 serving/day of chocolate consumption, respectively (P for trend = 0.02). For CVD mortality, compared to no chocolate consumption, the HRs (95% CIs) were 0.96 (0.91, 1.01), 0.88 (0.82, 0.95), 0.96 (0.93, 1.12) and 0.92 (0.80, 1.05) for <1 serving/week, 1–3 servings/week, 4–6 servings/week and ≥1 serving/day of chocolate consumption, respectively (P for trend = 0.45). For dementia mortality, compared to no chocolate consumption, the HRs (95% CIs) were 0.91 (0.84, 0.99), 0.89 (0.80, 0.99), 0.97 (0.79, 1.18) and 0.97 (0.80, 1.08) for <1 serving/week, 1–3 servings/week, 4–6 servings/week and ≥1 serving/day of chocolate consumption, respectively (P for trend = 0.95). Chocolate consumption was not associated with cancer mortality. Conclusions: Our results suggested modest inverse association of chocolate consumption with mortality from all-causes, CVD or dementia, specifically for a moderate chocolate consumption of ≤3 servings/week. Funding Sources: None.